Treatment of hook nails using the Bakhach's technique: a retrospective study - Francisco Milton da Silva; Marcelo Tavares Oliveira; Luiz Carlos Angelini; Wu Tu Chung (Sociedade Brasileira de Dermatologia (SBD), 2021)
Introduction: The cause of the hook nail is the trauma of the hyponychium. The nail plate presents longitudinal hypercurvature of volar concavity, causing functional loss, aesthetics concerns, and pain. Objective: To evaluate the research results of 20 medical records of patients submitted to hook nail correction surgeries of traumatic etiologies. Methods: Epidemiological, cross-sectional, retrospective study of patients' medical records who were submitted to Bakhach's surgical technique, from 2010 to 2018, in the Hand Surgery Outpatient Clinic of the Hospital do Servidor Público Municipal de São Paulo. Results: We analyzed 20 affected fingers: 7 were victims of accidents with sharp objects, 5 with press machines, 5 with doors, 1 with window, 1 with motorcycle, and 1 due to a dog bite. The finger with the highest incidence was the middle finger (n=12), followed by the index finger (n=5), and ring finger (n=3). The main complaint was aesthetics (n=11); pain (n=6), and functional (n=3). All cases had type II distal digital transverse amputations and underwent surgical treatment. The reconstruction surgery occurred between 4 and 25 months after the trauma. Conclusion: 15 patients were satisfied and two felt pain: one in the distal interphalangeal joint and the other in the hyponychium. The follow-up ranged from 6 months to 2 years.